The Machine Learning in Malware Detection: Muhammad Shairoze Malik - Malik, shairoze (International Journal for Electronic Crime Investigation, 2021)
Malware has become one of the biggest cyberthreats today with the rapid growth of the Internet. Malware can be referred to as any program that performs malicious acts, including data theft, espionage, etc. In a world of growing technology, protection should also increase at the same time. Machine learning has played a significant role in operating systems over the years. Cybersecurity is capable of using machine learning to boost organizations’detection of malware, triage, breach recognition and security alert. Machine learning will significantly change the cyber security climate. New techniques such as machine learning must be used to solve the rising malware problem. This paper aims to research how cybersecurity can be used for machine learning and how it can be used to detect malware. We will look at the PE (portable executable) headers of samples of malware and non-malware samples and create a classifier for malware that can detect whether or not malware is present